2010
DOI: 10.1111/j.1442-9071.2010.02373.x
|View full text |Cite
|
Sign up to set email alerts
|

Optic disc area and correlation with central corneal thickness, corneal hysteresis and ocular pulse amplitude in glaucoma patients and controls

Abstract: There was an inverse relationship between CCT and optic disc area in this study group. No association was found between optic disc area and OPA or CH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 24 publications
2
12
0
1
Order By: Relevance
“…Research studies have consistently reported that individuals with glaucoma have significantly lower CH measurements than healthy controls. 44,46 However, contradictory findings have been reported for CH measurements in individuals with keratoconus. Some studies have reported that mean CH measurements are significantly lower in individuals with keratoconus than normal individuals.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Research studies have consistently reported that individuals with glaucoma have significantly lower CH measurements than healthy controls. 44,46 However, contradictory findings have been reported for CH measurements in individuals with keratoconus. Some studies have reported that mean CH measurements are significantly lower in individuals with keratoconus than normal individuals.…”
Section: Discussionmentioning
confidence: 79%
“…27 The Ocular Hypertension Treatment Study (OHTS) noted that thinner CCT measurements are a risk factor for the development of primary open-angle glaucoma. 43 Moreover, previous studies have reported that eyes with thinner CCT measurements have larger 44,45 and deeper optic cups. Corneal hysteresis describes the viscoelastic characteristic of the cornea 4 and has been shown to vary in eyes with different ocular diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with the long-held belief that damage to components of the aqueous outflow pathways by reactive oxygen species (ROS) contributes to elevated IOP, a common feature observed in POAG (Siegfried et al, 2015). In other studies a correlation between CCT, optic nerve head topography, and visual field damage was found (Cankaya et al, 2008; Coman et al, 2014; Iester et al, 2012; Insull et al, 2010; Kaushik et al, 2006; Mokbel and Ghanem, 2010; Pakravan et al, 2007; Papadia et al, 2007; Saenz-Frances et al, 2015; Sullivan-Mee et al, 2005). The relationship between POAG risk and CCT is complex and poorly understood.…”
Section: Genetic Analyses Of Poag-associated Traits (Endophenotypes)mentioning
confidence: 73%
“…A previous study reported a relationship between cornea and optic disc dimensions and that the larger the cornea, the larger the optic disc (10) . Another study found a reverse relationship between CCT and the optic nerve area in primary open angle glaucoma patients and this relationship was shown to result in larger optic nerve areas with thinner corneas (11) . TDS is a congenital optic disc anomaly that affects the anterior and posterior segments of the eye.…”
Section: Discussionmentioning
confidence: 99%